Carbon nano-onions in composites: properties and application - Breczko, Joanna; Płońska-Brzezińska, Marta; Winkler, Krzysztof; Echegoyen, Luis (Видавництво Львівської політехніки, 2011)
A novel type of a composite made of small carbon nanoonions (CNOs) with poly(diallyldimethylammonium chloride) (PDDA) or chitosan (CHIT) was prepared and its electrochemical properties were investigated by cyclic voltammetry and electrochemical impedance spectroscopy. Solid composite films were prepared on the glassy carbon electrode surface by solvent evaporation from drop of solution containing CNOs with the filler (PDDA or CHIT). They form relatively porous structures, which exhibit typical capacitive behaviour, as well as excellent mechanical and electrochemical stability over a wide potential window. Better properties of the PDDA/CNOs and CHIT/CNOs composites in comparison with pure CNOs are hoped to allow them to be used in electrochemical sensing. Electrochemical properties of PDDA/CNOs film in PBS solution were examined and their ability to dopamine determination was verified. The composite can be applied not only to determination of a dopamine in a presence of ascorbic acid (AA) and uric acid (UA), but also let for simultaneous assays for all three biomolecules in the same solution.
Keywords: carbon nano-onions; polyelectrolytes; composites; dopamine; electrochemical sensing